2014
DOI: 10.1177/1933719114530186
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Postnatal Maternal Protein Intake on Prenatal Programming of Hypertension

Abstract: This study examined whether postnatal maternal dietary protein deprivation during the time of nursing can program hypertension when the offspring are studied as adults. Rats were fed either a 6% or 20% protein diet during the second half of pregnancy and continued on the same diet while rats were nursing their pups. The neonates of all of the rats were cross-fostered to a different mother and studied as adults. Adult rats that had a normal prenatal environment but were reared by mothers fed a low-protein diet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 57 publications
(113 reference statements)
0
31
0
1
Order By: Relevance
“…Rats in the 20% to 6% group and 6% to 6% group did not gain weight at the same rate as rats in the 6% to 20% group and 20% to 20% group, which was still apparent in the present study when rats were studied at 3 and 17 mo of age. We also found that optimizing the postnatal environment by cross-fostering neonatal pups on day 1 of life whose mothers were fed a low-protein diet during pregnancy to a mother that was fed a 20% control diet during pregnancy and while nursing (6% to 20% group) prevented the reduction in nephron number (14,36). Only 6% to 6% rats had a decrease in nephron number (36).…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…Rats in the 20% to 6% group and 6% to 6% group did not gain weight at the same rate as rats in the 6% to 20% group and 20% to 20% group, which was still apparent in the present study when rats were studied at 3 and 17 mo of age. We also found that optimizing the postnatal environment by cross-fostering neonatal pups on day 1 of life whose mothers were fed a low-protein diet during pregnancy to a mother that was fed a 20% control diet during pregnancy and while nursing (6% to 20% group) prevented the reduction in nephron number (14,36). Only 6% to 6% rats had a decrease in nephron number (36).…”
Section: Discussionmentioning
confidence: 86%
“…We have previously examined the effect of cross-fostering rats whose mothers were fed a 6% protein diet and a 20% protein diet during pregnancy and while nursing (36). Offspring were weaned and fed a 20% diet and studied at 2 mo of age.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations